A multi-road user evaluation of the acceptance of connected and automated vehicles through the lenses of safety and justice (2024)
As technological development towards connected and automated vehicles (CAVs) continues to rise, addressing the challenges associated with their integration is crucial, especially regarding public acceptance. This study explores the acceptability of CAVs, focusing on their potential role in enhancing safety and justice within the transport system. Semi-structured interviews were conducted with a diverse participant group, including 18 car drivers (aged 20–79, M = 48.3, SD = 18.77) and 12 pedestrians (aged 18–61, M = 36.0, SD = 12.94). Thematic analysis was employed to identify and contextualise factors influencing CAV acceptability, encompassing usefulness, ease of use, effectiveness, affordability, and social acceptability. Results emphasised safety as a top priority for both drivers and pedestrians. Trust and system reliability were also common concerns, varying with participants’ roles and transport experiences. Both drivers and pedestrians identified cost and economic benefits as significant barriers to CAV acceptance. Moreover, shared apprehensions about justice in adopting CAVs acknowledged the imperfections inherent in technological advancements. Participants supported CAVs but raised concerns about potential harm to vulnerable road users. Both car drivers and pedestrians expressed concerns that introducing CAVs could exacerbate existing injustices these road users face. This study offers valuable insights into how individual differences influence CAV acceptability, contributing to understanding their preparedness to adopt advanced automotive technologies.